Mortality Predictors in Elderly Patients With Cardiogenic Shock on Venoarterial Extracorporeal Life Support. Analysis From the Extracorporeal Life Support Organization Registry*. Issue 1 (January 2021) - Kowalewski, Mariusz; Zieliński, Kamil; Maria Raffa, Giuseppe; Meani, Paolo; Lo Coco, Valeria; Jiritano, Federica; Fina, Dario; Matteucci, Matteo; Chiarini, Giovanni; Willers, Anne; Simons, Jorik; Suwalski, Piotr; et al.
Abstract : OBJECTIVES: Because significantly higher mortality is observed in elderly patients undergoing venoarterial extracorporeal membrane oxygenation for refractory cardiogenic shock, decision-making in this setting is challenging. We aimed to elucidate predictors of unfavorable outcomes in these elderly (≥ 70 yr) patients. DESIGN: Analysis of international worldwide extracorporeal life support organization registry. SETTING: Refractory cardiogenic shock due to various etiologies (cardiac arrest excluded). PATIENTS: Elderly patients (≥ 70 yr). INTERVENTIONS: Venoarterial extracorporeal membrane oxygenation. MEASUREMENTS AND MAIN RESULTS: Three age groups (70–74, 75–79, ≥80 yr) were in-depth analyzed. Uni- and multivariable analysis were performed. From January 1997 to December 2018, 2, 644 patients greater than or equal to 70 years (1, 395 [52.8%] 70–74 yr old, 858 [32.5%] 75–79 yr, and 391 [14.8%] ≥ 80 yr old) were submitted to venoarterial extracorporeal membrane oxygenation for refractory cardiogenic shock with marked increase in the most recent years. Peripheral access was applied in majority of patients. Median extracorporeal membrane oxygenation support duration was 3.5 days (interquartile range: 1.6–6.1 d), (3.9 d [3.7–4.6 d] in patients ≥ 80 yr) ( p < 0.001). Weaning from extracorporeal membrane oxygenation was possible in 1, 236 patients (46.7%). Overall in-hospital mortality was estimated at 68.3% with highest crude mortality rates observed in 75–79 years old subgroup (70.1%). Complications were mostly cardiovascular and bleeding, without apparent differences between subgroups. Airway pressures, 24-hour pH after extracorporeal membrane oxygenation start, extracorporeal membrane oxygenation duration, and renal replacement therapy were predictive of higher mortality. In-hospital mortality was lower in heart transplantation recipients, posttranscatheter aortic valve replacement, and pulmonary embolism; conversely, higher mortality followed extracorporeal membrane oxygenation institution after coronary artery bypass + valve and in decompensated chronic heart failure, and nearly 100% mortality followed in extracorporeal membrane oxygenation for sepsis. CONCLUSIONS: This study confirmed the remarkable increase of venoarterial extracorporeal membrane oxygenation use in elderly affected by refractory cardiogenic shock. Despite in-hospital mortality remains high, venoarterial extracorporeal membrane oxygenation should still be considered in such setting even in elderly patients, since increasing age itself was not linked to increased mortality, whereas several predictors may guide indication and management. Abstract : Supplemental Digital Content is available in the text.